Validation of Multistatic Meteor Radar Analysis Using Modeled Mesospheric Dynamics: An Assessment of the Reliability of Gradients and Vertical Velocities. Issue 5 (8th March 2022) - Charuvil Asokan, Harikrishnan; Chau, Jorge L.; Larsen, Miguel F.; Conte, J. Federico; Marino, Raffaele; Vierinen, Juha; Baumgarten, Gerd; Borchert, Sebastian
Abstract: A virtual meteor radar system based on the upper‐atmosphere extension of the high‐resolution ICOsahedral Non‐hydrostatic general circulation model is constructed to validate multistatic specular meteor radar (SMR) analyses. The virtual radar system examines the validity of mean winds and gradients estimation techniques used in multistatic SMRs. The study is motivated by unexpected mean values and tide‐like features recently observed in the vertical velocities estimated from multistatic SMRs at different latitudes in the mesosphere and lower thermosphere. The proposed analysis confirms multistatic SMR systems' excellent capability to measure the horizontal mean wind components and gradient terms. It is also found that multistatic SMRs can estimate mean vertical winds if they have an amplitude greater than ±2 m/s. Due to the smoothing inherent to the model results, these results should be treated as lower bounds to the error incurred using real data. Hourly variability in vertical velocity estimates up to ±1–2 m/s in the observed vertical winds are due to contamination by small‐scale horizontal structures in the horizontal winds. Plain Language Summary: Specular meteor radars (SMRs) are a prominent ground‐based instrument to study the mesosphere and the lower thermosphere dynamics. Recently developed multistatic SMRs allow maximizing the number of measurements from different viewing angles, enabling the estimation of horizontal wind fields and their second‐order statistics (power spectrum, momentum fluxes). We have implemented the operational versions of these techniques in Germany, Peru, and Argentina called Spread‐spectrum Interferometric Multistatic meteor radar Observing Network (SIMONe) systems. We present a validation study of multistatic SMR analyses using virtual radar systems using as an input the prognostic fields obtained from the UA‐ICON general circulation model with a horizontal grid spacing of 5 km. The study focuses on the estimates of gradients and vertical velocities based on these multistatic systems. Key Points: Specular meteor radar (SMR) vertical velocities are assessed for the first time using a high‐resolution forward model The validation analyses suggest that mean horizontal winds and gradients estimation techniques used in multistatic SMRs work effectively Tide‐like periodicities observed in vertical winds using multistatic SMRs are not reproduced by horizontal wind component aliasing